'Of Pride and Joy No Common Rate': From the Surplus Women Problem to Surplus Jouissance in Margaret Oliphant's Hester. (20th July 2020) - Moore, Ben
Abstract: This article analyses Margaret Oliphant's novel Hester (1883), arguing that it dramatizes a complex interplay of surplus labour, surplus capital, the figure of the surplus woman, and surplus jouissance . The central character, Hester, is read as a figure who embodies the surplus jouissance which is both necessary to and disruptive of modern capitalism, and which in the novel stands in opposition to the steady state of the respectable country bank, taken here to align with the Freudian pleasure principle. In support of this reading, the article traces a line from Hester back to the 'surplus women debate' of the 1850s and 60s, including Oliphant's contribution to this debate in her 1858 article 'The Condition of Women'. The novel itself is analysed through its epigraph, taken from a Charles Lamb poem of 1803, and through the multiple meanings of the concept of 'chance' which the text presents. My analysis proceeds by way of Freud, J. S. Mill, Marx and Lacan, finding that Lacan's rereading of surplus labour as surplus jouissance ultimately provides the most productive way to read the text's rearticulation of the surplus women problem.